Archeology and separatism: the case of Val Camônica (Lombardy, Italy): Archeology and separatism: the case of Val Camônica (Lombardy, Italy) - Lo Monaco, Viviana (2022)
In Val Camônica (Brescia, Italy) there is the largest archaeological site of rock-art in Europe and its investigation began in the first half of the 20th century. Since then, the area has become increasingly important for the study of (so-called) prehistoric Europe and has played a highly representative role in the search for the ancient roots of the valley communities and, more generally, of northern Italy itself. In the late 1980s, the Lega Nord party (today the Lega party) was created, promoting the institution of an independent state called Padania. From that moment on, the themes of rock engravings were adopted, used and abused to disseminate ideologies and justify political intentions. The present text aims to briefly illustrate the dynamics behind the civil and political movement of the then Lega Nord and use of archaeology by institutions to forge the path towards the formation of a common European identity based on the history of Lombardy.